Mental capacity legislation principles and practice - Gunn, Michael; Holland, Anthony; Jacob, Rebecca (RCPsych Publications, 2013)
This book draws on clinical experience, case law and the developing research literature accrued during the six years that the Mental Capacity Act (MCA) and the Deprivation of Liberty Safeguards (DoLS) have been in effect. It focuses on the theory underpinning the principles of this legislation and the practical challenges of applying it in clinical settings. It also compares and contrasts the remit of the Mental Capacity Act with that of the Mental Health Act. The book is aimed at psychiatrists and other mental health professionals who treat individuals who lack capacity, and also at those called upon to guide and advise colleagues in acute hospitals and residential care settings about the assessment of capacity, DoLS and the appropriate use of best interests principles. The contributors, who include both clinicians and clinical academics, have been chosen to ensure that both practical and research considerations pertaining to the statute are taken into account. (Please note, this book applies to the law in England and Wales only.)
Keywords: Great Britain. -- Mental Capacity Act 2005.